Feminizing the Fetish Psychoanalysis and Narrative Obsession in Turn-of-the Century France - Apter, Emily (Cornell University Press, 1992)
Shoes, gloves, umbrellas, cigars that are not just objects-the topic of fetishism seems both bizarre and inevitable. In this venturesome and provocative book, Emily Apter offers a fresh account of the complex relationship between representation and sexual obsession in turn-of-the-century French culture. Analyzing works by authors in the naturalist and realist traditions as well as making use of documents from a contemporary medical archive, she considers fetishism as a cultural artifact and as a subgenre of realist fiction. Apter traces the web of connections among fin-de-siècle representations of perversion, the fiction of pathology, and the literary case history. She explores in particular the theme of "female fetishism" in the context of the feminine culture of mourning, collecting, and dressing.